Pentingnya Pemeriksaan Laboratorium Pada Ibu Hamil - Metty Nurherliyany; Dini Ariani; Sri Utami Asmarani; Dini Anggit Herdiani; Adinda Putri Maharani (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2023)
Introduction: The success of the maternal health program can be assessed through the main indicator, maternal mortality rate (MMR). One of the efforts that can be made to reduce MMR is the suggestion that health workers are expected to be able to prevent obstetric complications such as hypertension in pregnancy and the puerperium. Every pregnancy, in its development, has a risk of experiencing complications. Antenatal care must be carried out routinely, according to standards, and integrated for quality antenatal care. Antenatal care is very necessary for every pregnant woman because her condition greatly affects the continuity of pregnancy and the growth of the fetus in her womb. Laboratory tests are very important for the early detection of complications in pregnancy and childbirth so that they can be prevented and appropriate management carried out. Laboratory examination as a form of screening for the health conditions of pregnant women is a promotive, preventive, curative, and rehabilitative effort to prevent maternal and fetal morbidity and mortality provided by health workers. Objective: The purpose of this community service is to increase the mother's knowledge by providing health education on the importance of laboratory tests and performing hemoglobin, urine glucose, and urine protein examination services so that pregnant women can find out the condition of their pregnancy. Method: The implementation method is by providing health education and services for checking hemoglobin, urine glucose, and urine protein. Result: There were 13 pregnant women who did hemoglobin and urine tests, there were 11 pregnant women (84.6%) with non-anemia results and 2 pregnant women (15.4%) with anemia results. Then from the results of urine glucose and urine protein examinations, it was found that 13 pregnant women were all negative (100%). Conclusion: The target is very enthusiastic about participating in the activity. Pregnant women also feel very happy to be able to do their own pregnancy checks in an effort to detect early pregnancy complications that may occur. Laboratory tests found two pregnant women who had anemia during pregnancy, and all pregnant women had urine glucose and urine protein tests that were all negative.